Journey of change: Women navigation agricultural innovations - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu; Ketema, Dessalegn Molla; Waswa, Boaz Shaban (2024)
Women are not just victims but drivers of social change in the agrifood system. We are experiencing better resilience and transformation as women and men negotiate power, promoting partnership for shared dreams and mutual growth.